EFL Learners' Perceptions About Language Learning and Culture When Using Telecollaboration - Natalia Ramírez-Lizcano; María Alejandra Cabrera-Tovar (Universidad Nacional de Colombia, 2020)
This phenomenological study explores students' perceptions about the relationship between foreign language learning and culture when using telecollaboration. Three main concerns underlie this work: the lack of studies that explore how students perceive the relationship between foreign language learning and culture in the local context, the need to explore the incidence of culture in language learning, and the role of telecollaboration in cultural exchange. Data were collected through questionnaires, focus groups, video recordings, field notes, and students' artifacts. The findings show students' understanding of the nature of language situated within functional and humanistic perspectives. Furthermore, participants alluded to the importance of language learning as a means to understand the scope of culture and cultural identity.